คอมพอสิตของเทอร์โมพลาสติกพอลิยูรีเทน/พอลิโพรพิลีนกราฟต์มาเลอิกแอนไฮไดรด์/โวลลาสโทไนต์ - สุชัญญา เกตุทองมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
In this work, composites of thermoplastic polyurethane (TPU)/polypropylene-g-maleic anhydride (PP-g-MA)/wollastonite were prepared by melt mixing process. PP-g-MA was incorporated into TPU matrix in order to improve the dimensional stability of the TPU, whereas wollastonite was utilized to reduce cost and improve the mechanical strength and thermal stability of the composites. Wollastonite with particle size of 2000 mesh was used in this work. Extrusion compounding was performed by mixing TPU with different loadings of PP-g-MA and wollastonite. The extrudates were granulated and then fabricated into test specimens using either compression or injection molding machine. The effects of PP-g-MA and wollastonite on melt flow index, tensile properties, thermal stability, flammability and morphology of TPU were investigated using the melt flow indexer, universal testing machine, thermogravimetric analyzer, oxygen indexer and scanning electron microscope, respectively. The results showed that wollastonite plays an important role for improving not only the stiffness but also the thermal stability of the TPU. For TPU/PP-g-MA/wollastonite composites, the composition of 100/5/40 shows the optimal improvement in Young’s modulus and thermal stability. Moreover, specimens fabricated by injection molding provided better properties than those fabricated by compression molding.